A preliminary study on financial management practices among Kuala Nerus mosques - Wan Zakaria, Wan Zuriati; Ilias, Norazlina; Wahab, Norlidawahi; Wan Abdullah, Wan Zanani @ Zalani (UUM Press, 2020)
Each religion has its own institution and ways of dealing with all the religious-related matters in the community. For the Muslim community, the mosque, or known as "Masjid" in Arabic, is a place of worship for performing prayers and other religious-related activities. In conducting those activities, mosques usually receive funding from public donations, fundraising, "waqaf", the government and many more. Managing a mosque fund is crucial in order to build trust among the public, and simultaneously safeguard the mosques financial resources. Therefore, it is important for each mosque to adopt good financial management practices in managing funds effectively. The data for this study was collected through a questionnaire distributed to 23 respondents from 14 mosques in the district of Kuala Nerus, Terengganu, to explore their financial management practices. The descriptive analysis surprisingly shows that 79% of the mosques still use a manual system in managing their funds instead of a computerized accounting system. It is timely to develop a customized accounting system to cater the needs of mosques management to set up a systematic and efficient fund management.